The brink of poverty: Implementation of a social assistance programme in rural China - Lena Kuhn; Stephan Brosig; Linxiu Zhang (Journal of Current Chinese Affairs, 2016)
The Rural Minimum Living Standard is an important component of social security in rural areas of China, as it provides social assistance to poor rural households. The country's size and large development heterogeneities, however, make the policy's implementation a challenging task. Using quantitative and qualitative data from rural households and administrators in five provinces, we identify the pitfalls of multi-level implementation along with the difficulty of measuring income in rural, underdeveloped areas as key sources of an implementation gap that has led to a considerable degree of misallocation of monetary transfers. Changes in the budgeting process and the distribution method might improve the anti-poverty effect of social assistance without having to carry out additional monitoring.
Keywords: 330; China; rural China; social assitance; policy implementation